A case report of successful treatment of 90° knee flexion contracture in a patient with adult-onset Still's disease. Issue 1 (December 2016) - He, Qiang; Xiao, Lin; Ma, Jianbing; Zhao, Guanghui
Abstract Background Severe knee flexion contractures greater than 80° are rare and challenging to manage. Previous studies have demonstrated unsatisfactory clinical results after correcting these deformities because residual flexion contractures were not corrected within a short period of time. We herein report the case of a patient with adult-onset Still's disease with 90° of bilateral knee flexion contracture, which was successfully corrected by total knee arthroplasty and serial casting over a period of five weeks. Case presentation A 47-year-old male was admitted to our orthopedic department for bilateral knee pain and a preoperative fixed flexion contracture of 90°. A diagnosis of adult-onset Still's disease was made based on the patient's medical history of a high spiking fever, salmon-colored rash and bilateral knee and wrist pain. Bilateral total knee arthroplasty was carried out to address these deformities, but residual flexion contracture was present. Subsequently, serial casting was used to achieve full extension at four weeks after surgery. Excellent function and patient satisfaction were observed at two years of follow-up. Conclusion The new protocol of total knee arthroplasty with subsequent serial casting seems to be an efficient solution for knee flexion contractures greater than 80°. This report adds to the very small number of reported cases of adult-onset Still's disease with severe knee flexion contractures and describes a patient who was successfully treated with a new protocol.